Sustained delivery of acriflavine from the suprachoroidal space provides long term suppression of choroidal neovascularization. (June 2020) - Hackett, Sean F.; Fu, Jie; Kim, Yoo Chun; Tsujinaka, Hiroki; Shen, Jikui; Lima e Silva, Raquel; Khan, Mahmood; Hafiz, Zibran; Wang, Tao; Shin, Matthew; Anders, Nicole M.; He, Ping; et al.
Abstract: Hypoxia-inducible factor-1 (HIF-1) has been implicated in the pathogenesis of choroidal neovascularization (NV) and is an appealing target because it increases multiple pro-angiogenic proteins and their receptors. Acriflavine (ACF) binds HIF-1α and HIF-2α preventing binding to HIF-1β and inhibiting transcriptional activity of HIF-1 and HIF-2. Delivery of ACF to the eye by multiple routes strongly, but transiently, suppresses choroidal NV. We overcame design challenges and loaded highly water soluble ACF into poly(lactic-co-glycolic acid) (PLGA) microparticles (PLGA-ACF MPs) that release ACF in vitro for up to 60 days. Intravitreous injection of PLGA-ACF MPs in mice suppressed choroidal NV for at least 9 weeks and suprachoroidal injection of PLGA-ACF in rats suppressed choroidal NV for at least 18 weeks. Intravitreous, but not suprachoroidal injection, of PLGA-ACF MPs containing 38 μg of ACF in rabbits resulted in modest reduction of full-field electroretinogram (ERG) function. Over the span of 28 days after suprachoroidal injection of PLGA-ACF MP, rabbits had normal appearing retinas on fundus photographs, normal electroretinogram scotopic a- and b-wave amplitudes, no increase in intraocular pressure, and normal retinal histology. The active component of ACF, trypaflavine, had steady-state levels in the low nM range in RPE/choroid > retina for at least 16 weeks with a gradient from the side of the eye where the injection was done to the opposite side. These data suggest that suprachoroidal injection of PLGA-ACF MPs has the potential to provide a durable new treatment for retinal and choroidal vascular diseases. Graphical abstract: Suprachoriodal delivery of PLGA-ACF microparticles delivers pharmacologically relevant levels of ACF throughout the eye that significantly reduces development of laser-induced choroidal neovascularization in rats. The site of suprachoroidal injections is the same as that for intravitreous injections but the depth of penetration is different. Image 1